2021
DOI: 10.1093/mnras/stab3422
|View full text |Cite
|
Sign up to set email alerts
|

A NICER look at thermonuclear X-ray bursts from Aql X-1

Abstract: We present spectral and temporal properties of all the thermonuclear X-ray bursts observed from Aql X-1 by the Neutron Star Interior and Composition Explorer (NICER) between 2017 July and 2021 April. This is the first systematic investigation of a large sample of type I X-ray bursts from Aql X-1 with improved sensitivity at low energies. We detect 22 X-ray bursts including two short recurrence burst events in which the separation was only 451 s and 496 s. We perform time resolved spectroscopy of the bursts usi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
20
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 65 publications
7
20
1
Order By: Relevance
“…This increase is attributed to the increased mass accretion rate onto the neutron star, due to Poynting-Robertson (PR) drag caused by the burst emission, and supported by simulations of accretion disks illuminated by thermonuclear X-ray bursts (Fragile et al 2018(Fragile et al , 2020. Güver et al (2022) showed that the X-ray spectra can also be fit with models taking into account the reflection of the burst emission off the accretion disk.…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…This increase is attributed to the increased mass accretion rate onto the neutron star, due to Poynting-Robertson (PR) drag caused by the burst emission, and supported by simulations of accretion disks illuminated by thermonuclear X-ray bursts (Fragile et al 2018(Fragile et al , 2020. Güver et al (2022) showed that the X-ray spectra can also be fit with models taking into account the reflection of the burst emission off the accretion disk.…”
Section: Introductionmentioning
confidence: 78%
“…The soft X-ray sensitivity combined with the larger effective area of NICER allow for an effective time-resolved spectral study of thermonuclear X-ray bursts. Following previous studies (see, e.g., Güver et al 2022), we extracted timeresolved X-ray spectra for each burst, with varying exposure times, which depend on the total observed count rate from the source. To be able to catch the spectral evolution during the rise of the bursts, we used 0.5 s as a fixed exposure time up to the peak moment, and then allowed the exposure time to be longer.…”
Section: Time-resolved Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the burst oscillation candidate from XTE J1739-285 has been observed at 386.5 Hz (Bult et al 2021a), rather than 1122 Hz reported by Kaaret et al (2007). However, most of the sources have not reported the detection of burst oscillations (see, e.g., Aql X-1 and 4U 1636-536; Li et al 2021;Güver et al 2022;Zhao et al 2022).…”
Section: Introductionmentioning
confidence: 98%
“…Recently, the burst oscillation candidate from XTE J1739-285 has been observed at 386.5 Hz (Bult et al 2021a), rather than 1122 Hz reported by Kaaret et al (2007). However, most of sources have not been reported the detection of burst oscillations (see e.g., Aql X-1 and 4U 1636-536, Li et al 2021;Güver et al 2022;Zhao et al 2022), or the type-I X-ray bursts.…”
Section: Introductionmentioning
confidence: 97%